APPLICATION OF RACK AND PINION SIMULATOR IN BASIC COMPETENCY THE STEERING SYSTEM - Sidik, Asep Nurfajar; Sukrawan, Yusep; Komaro, Mumu (Universitas Pendidikan Indonesia, 2020)
This study aims to determine the increase in student learning outcomes after the application of rack and pinion simulators in the subject of chassis maintenance and power transfer systems. Learning basic competencies in understanding the steering system at SMK Negeri 1 Cisarua still does not use simulators because there are no such facilities. This study uses the Quasi Experiment method. Learning outcomes are known from the pretest and posttest scores and are proven by N-gain. The results showed that the application of rack and pinion simulators succeeded in increasing learning outcomes, seen from the increase in the average value of the experimental class from pretest 53.68 increased at posttest to 68.16. The N-Gain value of the experimental class doing learning using rack and pinion simulator media is 0.31 which is included in the medium category, while the N-Gain value of the control class conducting learning without using rack and pinion simulator media is only 0.19 included in the low category.